Mean ambient dose rate in various cities, inferred from Safecast data - Bossew, Peter; Kuča, Petr; Helebrant, Jan (Journal of environmental radioactivity, 2020)
Safecast is a citizen science project, aimed to environmental monitoring. Its main activity is measuring ambient dose rate all over the world. The freely accessible data, currently (January 2020) more than 120 million observations, were used to calculate mean values of dose equivalent rate in various cities where sufficient data is available. The results mainly reflect dose rate from terrestrial radiation, whose variability is controlled by the one of geochemistry, namely the concentrations of uranium, thorium and potassium. Further influence comes from cosmic radiation and in a few cases, from anthropogenic radiation caused by nuclear fallout. Mean dose rate has been calculated for 330 cities and towns worldwide. Results are shown in tables, graphs and as maps.
Keywords: Radiation Monitoring; monitorování radiace; radioaktivní látky znečišťující půdu; thorium; Cities; radioizotopy draslíku; velkoměsta; Radiation Dosage; Soil Pollutants, Radioactive; Uranium; Potassium Radioisotopes; uran; dávka záření; Thorium